The art of forgery : the minds, motives and methods of master forgers - Charney, Noah (London ; New York, NY : Phaidon, 2015)
The Art of Forgery: Case Studies in Deception explores the stories, dramas and human intrigues surrounding the world's most famous forgeries - investigating the motivations of the artists and criminals who have faked great works of art, and in doing so conned the public and the art establishment alike.
Includes bibliographical references (pages 277-282) and index.
Keywords: Art -- Forgeries; Forgery -- History